The Impact Of Colours On Visitors’ Attention In Proton Showroom, Malaysia - Al-Helly, Firas Hussein Ali (2014)
In an attempt to broaden the understanding of the physical environment's role on the visitor in the exhibition, this research investigated the impact of colour as a design element on the visitor's attention within the interior space of the auto-showrooms. The research focused on three variables which have been defined in depth. These variables are presented by colour as an independent variable, highlighting exhibits as a mediator, and the visitor’s attention was the dependent variable. This study developed a numeric scale to measure the impact of colour on the visitor’s attention, and practical experiment in order to answer the research question by both quantitative and qualitative approaches. The results showed that there are considerable relationships among the research variables, in other words there is a significant relationship between the colour and the visitor’s attention by highlighting the cars and brands within the interior space of the showroom. The findings were in line with the research objectives to serve the problem statement. This research has gained importance through the coincidence of the spatial and temporal dimensions. The researcher had observed that there is indifference in applying the interior design principles and elements in most of auto-showrooms; forgetting the basic goal of the establishing those showrooms is (to attract the visitor’s attention into the exhibits; not into the interior constructions). This research is a contribution to fill a gap in this field of knowledge, and it may open new horizons for future studies.